Intercity bus transportation system and its competition in Malaysia - Adji, B.M.; Roza, A.; Raja Abdul Aziz, R.S.; Karim, M.R. (2011)
Intercity transportation in Malaysia is quite similar to other countries, which involve three kinds of modes, namely, bus, rail and air. Among these modes, bus transportation continues to be the top choice for intercity travelers in Malaysia. Bus offers more flexibility compared to the other transport modes. Due to its relatively cheaper fare as compared to the air transport, bus is more affordable to those with low income. However, bus transport service today is starting to face higher competition from rail and air transport due to their attractive factors. The huge challenge faced by intercity bus transport in Malaysia is the management of its services. The intercity bus transport does not fall under one management; unlike rail transport which is managed under Keretapi Tanah Melayu Berhad (KTMB), or air transport which is managed under Malaysia Airports Holdings Berhad (MAHB). This paper discusses the competition between intercity buses and other modes.